Cultural intelligence - an essential competency in the globalised world. (22nd November 2022) - Leifels, Katrin; Turner, Michelle
The ability to interact effectively in cross-cultural settings has become a vital competency for members of international teams. This study explores the role of cultural intelligence (CQ) and its relationship to the functioning of culturally diverse teams. Thirty-four incidents perceived as stressful arising from working in a culturally diverse work team were explored using inductive thematic analysis and content analysis. Emergent themes were then categorised into the four dimensions of CQ (cognitive, behavioural, motivational and metacognitive) using a deductive approach. Communication and working style emerged as the key factors impacting on team interactions, and these were mostly aligned with the behavioural or cognitive dimensions of CQ. Lack of CQ can impact on collaboration and cohesion within culturally diverse teams, and the findings provide practical insights which can be utilised to prepare the workforce to develop this important competency.